Metformin mediates cardioprotection against aging‐induced ischemic necroptosis. Issue 2 (14th January 2020) - Li, Chen; Mu, Nan; Gu, Chunhu; Liu, Manling; Yang, Zheng; Yin, Yue; Chen, Mai; Wang, Yishi; Han, Yuehu; Yu, Lu; Ma, Heng
Abstract: Necroptosis is crucially involved in severe cardiac pathological conditions. However, whether necroptosis contributes to age‐related intolerance to ischemia/reperfusion (I/R) injury remains elusive. In addition, metformin as a potential anti‐aging related injury drug, how it interacts with myocardial necroptosis is not yet clear. Male C57BL/6 mice at 3–4‐ (young) and 22–24 months of age (aged) and RIPK3‐deficient ( Ripk 3 −/− ) mice were used to investigate aging‐related I/R injury in vivo. Metformin (125 μg/kg, i.p.), necrostatin‐1 (3.5 mg/kg), and adenovirus vector encoding p62‐shRNAs (Ad‐sh‐p62) were used to treat aging mice. I/R‐induced myocardial necroptosis was exaggerated in aged mice, which correlated with autophagy defects characterized by p62 accumulation in aged hearts or aged human myocardium. Functionally, blocking autophagic flux promoted H/R‐evoked cardiomyocyte necroptosis in vitro. We further revealed that p62 forms a complex with RIP1‐RIP3 (necrosome) and promotes the binding of RIP1 and RIP3. In mice, necrostatin‐1 treatment (a RIP1 inhibitor), RIP3 deficiency, and cardiac p62 knockdown in vivo demonstrated that p62‐RIP1‐RIP3‐dependent myocardial necroptosis contributes to aging‐related myocardial vulnerability to I/R injury. Notably, metformin treatment disrupted p62‐RIP1‐RIP3 complexes and effectively repressed I/R‐induced necroptosis in aged hearts, ultimately reducing mortality in this model. These findings highlight previously unknown mechanisms of aging‐related myocardial ischemic vulnerability: p62‐necrosome‐dependent necroptosis. Metformin acts as a cardioprotective agent that inhibits this unfavorable chain mechanism of aging‐related I/R susceptibility. Abstract : Metformin treatment restores autophagy flux in aged hearts and decreases p62 interaction with necrosomes in I/R‐injured myocardium, ultimately reducing mortality in this model. We conclude that p62 accumulation provides a direct link between aging and the onset of necroptosis enhancement in a pathophysiological context.